A tale of two cohorts: identifying differences in group work perceptions. Issue 1 (5th May 2015) - Prokofieva, Maria; Jackling, Beverley; Natoli, Riccardo
Abstract : Purpose: – The purpose of this paper is to investigate group work perceptions of international and domestic accounting students. Although prior studies have demonstrated differences between domestic and international students in terms of their generic skill development, the present study explores this development via the use of a group work assessment task and offers practical suggestions for accounting instructors. Design/methodology/approach: – This paper utilises non-parametric tests (Mann-Whitney) and a thematic analysis to identify differences between the two accounting student cohorts. Findings: – The findings reveal that international accounting students were more optimistic about participating in group work and enjoyed higher levels of perceived generic skill development arising from the group work activity. However, domestic students gained more in terms of discipline-specific content knowledge while language barriers between the two cohorts were viewed as an obstacle to effective group work. Research limitations/implications: – This study is based on the data collected from a single university and would benefit with replication at other institutions. For accounting educators of similar cohorts, suggestions are given as to how group work activities can be incorporated into an effective teaching practice. Originality/value: – The study contributes to the existing literature by examining differences between international and domestic accounting students' attitudes of group work and their perceived generic skill development.